TRP Channels in Angiogenesis and Other Endothelial Functions - Smani, Tarik; Gómez, Luis J.; Regodon, Sergio; Woodard, Geoffrey E.; Siegfried, Geraldine; Khatib, Abdel-Majid; Rosado, Juan A. (Frontiers in Physiology, 2018)
Angiogenesis is the growth of blood vessels mediated by proliferation, migration, and spatial organization of endothelial cells. This mechanism is regulated by a balance between stimulatory and inhibitory factors. Proangiogenic factors include a variety of VEGF family members, while thrombospondin and endostatin, among others, have been reported as suppressors of angiogenesis. Transient receptor potential (TRP) channels belong to a superfamily of cation-permeable channels that play a relevant role in a number of cellular functions mostly derived from their influence in intracellular Ca2+ homeostasis. Endothelial cells express a variety of TRP channels, including members of the TRPC, TRPV, TRPP, TRPA, and TRPM families, which play a relevant role in a number of functions, including endothelium-induced vasodilation, vascular permeability as well as sensing hemodynamic and chemical changes. Furthermore, TRP channels have been reported to play an important role in angiogenesis. This review summarizes the current knowledge and limitations concerning the involvement of particular TRP channels in growth factor-induced angiogenesis.